PERLINDUNGAN HUKUM PEMEGANG HAK DESAININDUSTRI KEMASAN DALAM PENERAPAN NOVELTY(STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR162 K/Pdt.Sus-HKI/2021) - Mellenia (2022)
This study aims to determine the implementation of the application of novelty which in practice there are problems in the legal protection of industrial design. An industrial design will get legal protection if it is registered and novelty (considered new). One of the problems with the application of novelty is that designs that are not new can be registered, for example Ruben Onsu can register an industrial design for geprek chicken food packaging where the registered design is the same as Benny Sujono's which had previously been registered with the Directorate General of Intellectual Property Rights. This study uses a normative juridical approach. The results of this study indicate the emergence of problems in the implementation of the application of novelty in the legal protection of industrial design. This is because the existing law does not clearly regulate it. For this reason, it is necessary to revise the applicable regulations and also to the competent body to carry out a more substantive examination of the registered industrial designs. Keywords : Protection Law, Industrial Designs, Novelty